Seasonal variation of salinity of ground water at Patenga area of Chittagong district in Bangladesh (Progressive Agriculture, 2019)
Availability of safe drinking water is scarce in the coastal areas of Bangladesh due to saltwater intrusion in fresh water aquifer. Patenga, a densely populated coastal area within Chittagong city corporation area, is not under the municipal water supply coverage. The groundwater of Patenga is contaminated by higher concentration of chloride and total dissolved solid. This study aims to investigate the water quality of the tube well based on its distance from flood protection embankment to observed saltwater intrusion in fresh water aquifer. Water sample were collected several times from different tube wells at patenga area based on tube well’s distance from  embankment from February 2017 to August 2017 to observe the seasonal variation of water quality. It was found that chloride concentration, electric conductivity, total dissolved solids etc. are very high compared to the standard value for drinking purpose in Bangladesh. The chloride concentration also decreased as the distance of the tube-wells from embankment increased, which implies that tube well near to coast line has higher chloride concentration. It was also observed that chloride concentration in tube well water also increased during dry season. In this study, the location of the tubewells were considered only along a single alignment in the perpendicular direction of the coastal bank. The study can be further extended for more offsets both in the parallel and the perpendicular direction of the coastal bank for better understanding of the groundwater salinity intrusion.Progressive Agriculture, Vol. 30, Suppl. 1: 65-70, 2019